Application of the Fuzzy Approach to Agricultural Production Planning in the Atrak Watershed Iran - Mohaddes Hosseini, Seyed Ahmad (2005)
The Atrak watershed is located in the northeast of Iran, where agricultural production is the main activity of the area. The government of Iran has adopted a sustainable agricultural development strategy for all watersheds in the country including the Atrak watershed. The government's goal is to embark on a sustainable agricultural development that not only provides the production of agricultural commodities and employment but also protects the environment from degradation. The rationale of adopting this strategy is that the watersheds of Iran, including the Atrak watershed, are facing many environmental problems especially severe soil erosion. The main purpose of this study is to define a framework for sustainable agricultural production planning for these watersheds particularly for Atrak watershed. \I1atersheds are large-scale regions ~Vhere agricultural production planning is usually associated n.ith multiple objectives including economic, social and environmental targets. Uncertainty plays an important role in all agricultural planning because some factors are not fully controllable and some input data or parameters such as demand, resources, costs and objective functions are imprecise. This study develops and applies fuzzy multi-objective mathematical programming models to the Atrak watershed agricultural development plan. The models include three objectives, namely, profit maximization, employment maximization and erosion minimization, and they are subject to 89 constraints. The models focus on sustainable agricultural production planning in order to determine the optimal cropping patterns in short-term and intermediate-term planning of the Atrak watershed. Results of the models show that the most important crops in the optimal plans in short and mid term are wheat, orchards (grape and other orchards) and alfalfa. Compared to current crop pattern, the results show that if the optimal plan was implemented, the optimal value of profit and employment would have increased respectively by 16.12 and 0.53 percent and erosion decreased by 19.88 percent. These figures may not show significant changes to the existing crop pattern, however it would improve farmers' income, and at the same time, achieve more sustainable agricultural development. The Atrak \\'atershed consists of eight zones. In this study, cropping patterns for all the zones are also determined. The model is also applied to several scenarios, i.e. looking at different tradeoffs among different but conflicting objectives (using different weights). The result shows a high profit is achievable while pursuing erosion control and higher employment, whereas there are trade-offs between economic, environmental and social targets. In addition, the result also shows that if the decision maker insists on higher employment level, profit level will fall and the erosion will increase. Therefore, the decision maker should not expect more employment from agricultural sector of Atrak watershed. Where equal weights are given to the various objectives, the result shows that social goal (employment) and environmental goal (erosion) were more attainable over economic goal (profit) in the Atrak Watershed. The study also compares the results from the fuzzy model with a nonfuzzy model. In the case of non-fuzzy model, goal programming (GP) formulation is used because GP is capable of handling multiple objectives and it is recognized as a useful tool for agricultural planning. This comparison indicates that the fuzzy linear multi-objectives model is superior to the nnn-fuzz\- linear techniques such as linear and goal y rogran~mingm odels.